1999
DOI: 10.1046/j.1439-0507.1999.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of dermatomycoses of humans in Central Poland. Part IV. Onychomycosis due to dermatophytes

Abstract: The total number of dermatophytoses (7393) included 1567 (21.2%) cases of onychomycosis. Etiological factors in descending order were: Trichophyton rubrum (58.8%), Trichophyton mentagrophytes var. granulosum (26.2%), T. mentagrophytes var. quinckeanum, T. mentagrophytes var. interdigitale (5.1%), Trichophyton tonsurans (4.1%), Trichophyton violaceum (1.5%), Trichophyton spec. (1.1%). An increase in the incidence was noted between 1994 and 1996. At present, onychomycosis is third by incidence among all clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Recently, numerous authors reported similar findings. [9][10][11][12] In our study, most of the infections due to T. rubrum were found in adults, which was consistent with the observations of Desai and Bhat [6] and Ng et al . [13] Adults had a higher susceptibility to T. rubrum infections than children.…”
Section: Discussion Discussionsupporting
confidence: 92%
“…Recently, numerous authors reported similar findings. [9][10][11][12] In our study, most of the infections due to T. rubrum were found in adults, which was consistent with the observations of Desai and Bhat [6] and Ng et al . [13] Adults had a higher susceptibility to T. rubrum infections than children.…”
Section: Discussion Discussionsupporting
confidence: 92%
“…The prevalence of the different dermatophyte species varies with changes in geographic and climate conditions and also depends on affected body site. In Europe, M. canis is the most prevalent cause of tinea capitis and this could be related to close association of humans with their pets, and T. rubrum of tinea pedis and tinea corporis 9,11,12,16–18 . In Croatia, we observed an outbreak of M. canis infection within the last two decades.…”
Section: Discussionmentioning
confidence: 82%
“…In Europe, M. canis is the most prevalent cause of tinea capitis and this could be related to close association of humans with their pets, and T. rubrum of tinea pedis and tinea corporis. 9,11,12,[16][17][18] In Croatia, we observed an outbreak of M. canis infection within the last two decades. Differences between regions also exist.…”
Section: Discussionmentioning
confidence: 95%
“…Kastelic and Wolf 3 found that T. mentagrophytes dominated in the Rijeka area since 1957. It is also one of the most frequent dermatophytes in other Croatian areas 4–6 as well as in other European countries, such as northern and central Poland (accounting for 30–45% of all dermatophytes), 7–10 northern Finland (26%) 11 and Italy (10.6%), 12 but appears to be declining in Mexico 13…”
Section: Discussionmentioning
confidence: 99%
“…Since Second World War, fungal infections caused by T. rubrum had become widespread 11 . Recently, the isolation rate of this dermatophyte is very high in the majority of European countries such as Greece, 23 Finland, 11 Poland, 7–9 Italy, 2,15 Slovakia, 24 as well as United States, 25 South America 13,22,26 and some parts of Asia 17,22 . However, in our study, T. rubrum infection was observed in Rijeka area only occasionally.…”
Section: Discussionmentioning
confidence: 99%